Marketing Library and Information Services: International Perspectives - Dinesh K. Gupta , Christie Koontz (K. G. Saur Verlag GmbH, 2006)
Strategic marketing management is based on an organisation-wide marketing orientation that focuses strategic planning and management on the client; continuous market research; integrated activities and repeat business due to satisfied customers. Australian university libraries have been very successful in using the concept of market orientation to provide a framework for applying marketing principles to their management and service operations. This paper uses the seven Ps of services marketing to identify some strategies and operations that Australian university libraries have implemented as market oriented organisations. Issues discussed include market research, client segments, market positioning, product definitions, placement, processes, price, staffing and marketing communications